IDENTIFIKASI FAKTOR FAKTOR YANG BERKONTRIBUSI DALAM PENGEMBALIAN REKAM MEDIS DI UPT PUSKESMAS MKG - Husin, Husin; Mursid, Mursid; Ningsih, Eka Rahma (Politeknik Unggulan Kalimantan, 2024)
The return of medical records is often not on time at the MK Health Center. The results of the observation showed that 55.45% of medical records were returned late in less than 2x24 hours and 44.55% of medical records were returned within 14x24 hours. This study aims to provide an overview of the factors that play a role in the return of medical records and to identify the occurrence of Incomplete Medical Records (IMR) and Delinquent Medical Records (DMR) at the MK Health Center during the Third Quarter of 2022. The design of this study is more qualitative with a case study design with 4 informants. The selection of research subjects used purposive, while the medical records analyzed were medical records in the third quarter of 2022. Data collection through observation and interviews. The results of the study identified human resource factors, namely lack of discipline, knowledge and motivation of officers and high workload factors in completing and returning medical records on time, as well as standard operating procedure (SOP) factors. The incidence of incomplete medical records (IMR) was 45.92% and delinquent medical records (DMR) was 100% based on medical records returned to the storage room being stored directly without any analysis of the completeness of the filling by the officer.